Effects of PTPN6 Gene Knockdown in SKM-1 Cells on Apoptosis, Erythroid Differentiation and Inflammations - Li Yu; Xiaoli Gu; Pengjie Chen; Rui Yang; Yonggang Xu; Xiupeng Yang (Current Issues in Molecular Biology)
Objective: Protein tyrosine phosphatase non-receptor type 6 (PTPN6) is a cytoplasmic phosphatase that acts as a key regulatory protein in cell signaling to control inflammation and cell death. In order to investigate the role of PTPN6 in hematologic tumor myelodysplastic syndrome (MDS), this study infected SKM-1 cell line (MDS cell line) with packaged H_PTPN6-shRNA lentivirus to obtain H_PTPN6-shRNA SKM-1 stable strain. The effect of PTPN6 knockdown on apoptosis, erythroid differentiation, and inflammations in SKM-1 cell line was examined. Methods: The stable knockdown SKM-1 cell line was validated using qPCR and Western blot assays. The proliferation activity, apoptosi, erythroid differentiation, and inflammatory cytokines in SKM-1 cells were assessed before and after transfection. Results: qPCR confirmed that the expression level of H_PTPN6-shRNA in SKM-1 cells was significantly reduced, and Western blot showed that the protein expression level of H_PTPN6-shRNA in SKM-1 cells was also significantly reduced. The CCK-8 cell viability assay confirmed that stable gene knockdown did not affect cell viability. Flow cytometry revealed that the apoptosis rate of cells in the PTPN6 knockdown group was 0.8%, lower than the 2.7% observed in the empty plasmid group; the expression rate of the erythroid differentiation marker CD235a was 13.2%, lower than the 25.0% observed in the empty plasmid group. The expression levels of the proinflammatory factors IL-6 and IL-8 increased, and the expression levels of the inhibitor factor IL-4 decreased. Conclusions: The PTPN6 gene was successfully knocked down using lentivirus-mediated transduction, and the constructed cell line was validated using PCR and Western blot. The CCK-8 cell viability assay confirmed that stable gene knockdown did not affect cell proliferation viability. Flow cytometry analysis of apoptosis and erythroid differentiation indicated that PTPN6 knockdown inhibits apoptosis and erythroid differentiation in SKM-1 cells and also alters the level of inflammations in the bone marrow microenvironment. It suggests that the PTPN6 gene acts as a tumor suppressor in myelodysplastic syndrome cells, influencing hematopoietic cell apoptosis, erythroid differentiation, and inflammations. This provides a reliable experimental basis for further in-depth studies on the mechanism of PTPN6 in MDS and related pharmacological research.